Innovations in research ethics governance in humanitarian settings - Schopper, Doris (BMC Med Ethics, 2015)
BACKGROUND: Médecins Sans Frontières (MSF) is one of the world’s leading humanitarian medical organizations. The increased emphasis in MSF on research led to the creation of an ethics review board (ERB) in 2001. The ERB has encouraged innovation in the review of proposals and the interaction between the ERB and the organization. This has led to some of the advances in ethics governance described in this paper. DISCUSSION: We first update our previous work from 2009 describing ERB performance and then highlight five innovative practices: • A new framework to guide ethics review • The introduction of a policy exempting a posteriori analysis of routinely collected data • The preapproval of “emergency” protocols • General ethical approval of “routine surveys” • Evaluating the impact of approved studies The new framework encourages a conversation about ethical issues, rather than imposing quasi-legalistic rules, is more engaged with the specific MSF research context and gives greater prominence to certain values and principles. Some of the innovations implemented by the ERB, such as review exemption or approval of generic protocols, may run counter to many standard operating procedures. We argue that much standard practice in research ethics review ought to be open to challenge and revision. Continued interaction between MSF researchers and independent ERB members has allowed for progressive innovations based on a trustful and respectful partnership between the ERB and the researchers. In the future, three areas merit particular attention. First, the impact of the new framework should be assessed. Second, the impact of research needs to be defined more precisely as a first step towards being meaningfully assessed, including changes of impact over time. Finally, the dialogue between the MSF ERB and the ethics committees in the study countries should be enhanced. SUMMARY: We hope that the innovations in research ethics governance described may be relevant for other organisations carrying out research in fragile contexts and for ethics committees reviewing such research.